Scoping review of resources for integrating evidence-based supported employment into spinal cord injury rehabilitation. Issue 14 (3rd July 2019) - Cotner, Bridget A.; Ottomanelli, Lisa; Keleher, Virginia; Dirk, Lynn
Abstract: Purpose: Individual placement and support (IPS), an evidence-based supported employment (SE) program, has helped Veterans with spinal cord injury (SCI) receiving care in the Veterans Health Administration to obtain work. To facilitate integration of IPS into SCI rehabilitation, resources are needed. A scoping review was conducted to identify tools and resources suitable for providers of SCI care. Methods: Applying a modified version of Arksey and O'Malley's framework, a scoping review of literature on SE tools or resources was conducted. The original review focused on resources published between 2002 and 2015 and available in English. Prior to publication an updated review through 2017 was conducted. Results: From 1822 tools and resources identified in the initial review, 24 met criteria for inclusion and were evaluated by an advisory panel of experts, who selected 16 tools that addressed five topics: IPS in SCI ( n  = 2) orientation to SCI ( n  = 3); IPS SE ( n  = 7), job accommodations ( n  = 2), and benefits planning ( n  = 2). The updated review yielded no tools or resources that met inclusion criteria. Conclusion: Despite few resources to guide implementation of IPS in SCI, 16 essential resources were identified that, combined into a toolkit, may facilitate translation of IPS in SCI from research to clinical care. Implications for rehabilitation: The toolkit consists of 16 essential resources and is currently available online to all persons involved in spinal cord injury rehabilitation to educate them about this effective means of assisting persons with spinal cord injury to find employment and to facilitate translation of individual placement and support in spinal cord injury from research to clinical care. While expert-informed, the toolkit is being field tested with both clinical and vocational providers to facilitate the adoption of individual placement and support by spinal cord injury rehabilitation programs. The revised version will be made available online.